Implikatur Perundungan Verbal pada Film Budi Pekerti dan Implikasinya dalam Pembelajaran Bahasa Indonesia: Studi Pragmatik - Sahira, Luthvi Aulia; Fuad, Muhammad; Prasetyo, Heru (Universitas Muhammadiyah Kotabumi, 2025)
This study explores the conversational implicature that represents verbal bullying in the movie Budi Pekerti directed by Wregas Bhanuteja as well as describes its implication in Indonesian language learning in high school. The main purpose of this research is to comprehensively describe the types of implicature contained in the bullying dialog and examine its relevance in learning. This research applies a qualitative approach with descriptive method. The data analyzed were dialogues between characters containing verbal bullying, which were collected through listening and note-taking techniques. The research findings show that there is a variety of implicatures, both conventional and unconventional, in the movie conversations. The dominance of unconventional implicatures indicates the significance of context in interpreting the meaning of bullying. This shows the relevance of the sociocultural context regarding the phenomenon of bullying that can be implied in Indonesian language learning in the form of LKPD on drama appreciation in class XI senior high school.